Evaluation of Differential Physiological and Biochemical Response of Sugarcane (Saccharum spp. Complex cv. Co 94012) Parent and Mutant’s in Response to Salt Stress - Gadakh, S. S.; Patel, D. U.; Ban, Y. G. (International Journal of Bio-resource and Stress Management, 2017)
The present investigation carried out at Main Sugarcane Research Station, Navsari Agricultural University, Navsari during 2011−2014 to develop salt tolerance lines in sugarcane. Sugarcane mutants against salt tolerance were derived using in vitro mutagenesisand regeneration under NaCl stress. Sugarcane cv. 94012 was used for callus development from meristimatic leaf whorl on MS medium supplemented with 4 mg/l 2,4-D+2% sucrose. At treatment of Ethyl Methane Sulphonate (0.5%) for 2 hours treatment 48.60% calli survived similarly out of four concentration of NaCl 100 mM concentration of NaCl give at least 50.20% survived of calli. So these concentrations were used for development of salt tolerant mutant in sugarcane. The calli were treated with EMS lethal dose (LD50) placed on shoot regeneration media containing LD50 concentration of NaCl. The plants which regenerated from the tolerant calli were grown in pot culture system under five levels of salinity stress as compared to parental plants (source variety). With increasing supply of NaCl, root growth was more adversely affected. The growth of shoot, Chlorophyll content, photosynthesis rate, stomatal conductance and dry matter showed a decreasing trend but it shows significantly slow rate in tolerant mutants than parental plants. Mutant plants performed significantly well than parental plants in salt stress condition in all physiological and biochemical parameters. The result showed that high salt concentration Na+ content in shoot of tolerant mutant and but was less than the normal plant. While, K+ content in shoot was high in tolerant mutants than normal plants.